2005
DOI: 10.5194/acp-5-1125-2005
|View full text |Cite
|
Sign up to set email alerts
|

The aerosol-climate model ECHAM5-HAM

Abstract: Abstract. The aerosol-climate modelling system ECHAM5-HAM is introduced. It is based on a flexible microphysical approach and, as the number of externally imposed parameters is minimised, allows the application in a wide range of climate regimes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
1,069
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,040 publications
(1,110 citation statements)
references
References 101 publications
39
1,069
1
1
Order By: Relevance
“…ECHAM6-HAM2 predicts the evolution of micro-physically interacting aerosol populations, their size distribution and composition (Stier et al, 2005;Zhang et al, 2012). For all our simulations, we use model version ECHAM6.1.0-HAM2.2.…”
Section: Echam6-ham2mentioning
confidence: 99%
See 1 more Smart Citation
“…ECHAM6-HAM2 predicts the evolution of micro-physically interacting aerosol populations, their size distribution and composition (Stier et al, 2005;Zhang et al, 2012). For all our simulations, we use model version ECHAM6.1.0-HAM2.2.…”
Section: Echam6-ham2mentioning
confidence: 99%
“…For details on the implementation of sedimentation, wet and dry deposition, thermodynamics and aerosol micro-physics parametrization, see Stier et al (2005). A detailed assessment of the processes which drive the evolution of aerosol mass and number concentrations is described in Schutgens and Stier (2014).…”
Section: Echam6-ham2mentioning
confidence: 99%
“…The approach for below-cloud scavenging does not differentiate between soluble and insoluble aerosol modes (Stier et al, 2005) but between aerosol mass and number as shown in Table 2. Values are updated based on the work by Croft et al (2009) and are substantially lower than the previously used values based on Dana et al (1975).…”
Section: Aerosols and Wet Depositionmentioning
confidence: 99%
“…These changes are documented in this paper. In the current version, in-cloud scavenging is different for liquid, mixed and ice stratiform clouds (Stier et al, 2005). This distinction is based on the local temperature (Croft et al, 2010), where clouds are assumed pure liquid above 0 • C and pure ice below −35 • C. Between these boundaries, the clouds are classified as mixed as shown in Table 1.…”
Section: Aerosols and Wet Depositionmentioning
confidence: 99%
See 1 more Smart Citation